Pengaruh Temperatur dan Rasio H2/Hidrokarbo Menggunakan Katalis CoMo/Î³-Al2O3 pada Hydrotreating Combined Gas Oil - Sucipto, Lukman; Rustyawan, Wawan; Jumaeri, Jumaeri; Alighiri, Dante; Wahyuni, Sri (Indonesian Journal of Chemical Science, 2019)
Catalytic hydrodesulfurization of Combined Gas Oil (CGO) was used CoMo/ -Al2O3 catalyst. The reaction was carried out at the trickle bed reactor with temperature 265, 300, 300, 330Â°C and H2/Hydrocarbons ratio 288 and 310 m3/m3; pressure 65atm and LHSV 1.8 h-1. The study aims to determined the effect of H2/Hydrocarbons ratio and temperature in reducing sulfur content from CGO feeds. The Hydrotreating products were analyzed by Total Nitrogen Total Sulfur (TNTS), Gas Chromatography Mass Spectrometry (GC-MS), and Fourier Transform Infra Red (FTIR). HDS product spesifications also analyzed using picnometer, Total Acid Number (TAN), and Doctor test Solution. The results of the analysis catalytic HDS test showed that the temperature range of 265-330Â°C increased and the H2/Hydrocarbons ratio 288-310 Nm3/m3, the HDS conversion was increased until 91.94%. The value of rate HDS (kHDS) also increased with temperature and H2/Hc ratio until 1,46x10-7 s-1. The minimum energy activation required by the catalytic hidrodesulfurization reaction in ratio H2/Hc 288 m3/m3 was 54,25 kJ/mol. Keywords : hydrotreating, Catalyst CoMo/ -Al2O3, temperature, H2/Hc ratio